From automation to collaboration: exploring the impact of industry 5.0 on sustainable manufacturing - Md. Abdus Shabur; Abid Shahriar; Mst. Anjuman Ara (Discover Sustainability)
Abstract Industry 5.0 represents a significant shift from the automation-centric paradigm of Industry 4.0, emphasizing human–machine collaboration, sustainability, and resilience in industrial operations. This study explores the integration of advanced technologies such as artificial intelligence (AI), collaborative robotics, human-digital twins (HDTs), and the Internet of Things (IoT) with human creativity to drive sustainable and adaptive manufacturing processes. Through a systematic literature review (SLR) of 110 articles, this research identifies key drivers, challenges, and opportunities associated with Industry 5.0. The findings highlight Industry 5.0’s role in enhancing mass customization, reducing environmental impact through circular economy principles, and improving workforce adaptability through reskilling initiatives. Despite its potential, challenges such as technological integration, ethical AI concerns, regulatory barriers, and cybersecurity risks remain critical hurdles to adoption. This study also proposes a structured Industry 5.0 framework, outlining key implementation steps, including human-technology integration, ethical compliance, sustainable manufacturing strategies, workforce adaptation, and real-time optimization. The research contributes to existing literature by providing a comparative analysis of Industry 4.0 and Industry 5.0, testable hypotheses for future empirical validation, and insights into policy and industrial strategies for seamless transition. The study concludes that Industry 5.0 is not just an extension of Industry 4.0 but a transformative paradigm aimed at fostering a sustainable, human-centric industrial future. The findings provide actionable strategies for industry leaders, policymakers, and researchers to navigate the evolving industrial landscape effectively.